Cost-benefit assessment of 2D and 3D climate and weather optimized trajectories - Lührs, Benjamin; Niklaß, Malte; Frömming, Christine; Grewe, Volker; Gollnick, Volker (2016)
Climate optimized flight trajectories are considered to be a promising measure to mitigate non-CO2 emissions’ environmental impact, which is highly sensitive to locus and time of emission. Within this study, optimal control techniques are applied in order to determine 2D (lateral) and 3D (lateral and vertical) cost-optimized flight trajectories while mitigating their climate impact by minimizing emissions and flight time in highly climate sensitive regions. Therefore, monetary and 4D-climate cost functions, describing the climate sensitivity in dependency of the emission location, altitude, time and weather situation, are integrated into the optimization algorithm. For both, 2D- and 3D-optimization, the cost-benefit potential (climate impact mitigation vs. rise in operating costs) is investigated for nine fictitious North Atlantic routes for eastbound and westbound directions in the presence of winds. The conducted study shows large potential for both measures as the reduction of climate sensitivities along the trajectory often predominates the additional emissions caused by headwinds, additional climb-and descent phases, additional flight distance, and off-design altitudes. Flight trajectories optimized within the horizontal plane can reduce the average temperature response (ATR) by approximately 15 % for a two percent increase in cash operating costs (COC). This mitigation potential is significantly improved by superposition of lateral and vertical optimization. 3D-optimized trajectories which are comparable in cost increase achieve a 20-35 % higher ATR reduction than their 2D-optimized counterparts. Further, they reduce global warming more efficiently (higher ATR reduction per unit cost increment) and to a higher extent. However, achieving maximum climate impact mitigation is linked with an disproportional rise of cash operating costs in both cases. Therefore, a careful consideration of the required climate impact savings as well as the accepted surcharges is necessary.